Finite Element analysis of local buckling in cold-formed steel rack columns with edge-stiffened holes (Revista Brasileira Multidisciplinar, 2025)
Cold-formed steel sections are an efficient and economical way to build structural columns. They have high slenderness due to their low thickness, thus are prone to global, local and distortional buckling. They usually have holes to fit connections or instalations, that may reduce their resistance and make their behaviour more complex. To reduce its holes bad effects, their edges may be stiffened. This work analyzes the efficiency of edge-stiffened rectangular holes in cold-formed rack colums. Finite Element analysis by software ANSYS was used to evaluate colums without holes, with non-stiffened holes, with holes containing one lateral edge stiffened end with holes containing tho lateral edges stiffened. Results indicated that adoption of one edge-stiffened lateral holes avoided local buckling between holes with lenght up to 20% higuer than columns web width, and the two edge-stiffened holes up to lenght 30% higuer than columns web width. Due to similar efficiency and considering the usual assemblage of industrial storage systems, a one edge-stiffened hole may be a reccomendation to practical uses.
Keywords: Cold-formed steel rack sections; finite element, edge-stiffened holes, local buckling.